Chronic exposure to IQOS results in impaired pulmonary function and lung tissue damage in mice. (1st February 2023) - Gu, Jianjun; Gong, Daohui; Wang, Yuxiu; Feng, Tingting; Zhang, Jun; Hu, Suwei; Min, Lingfeng
Abstract: The use of IQOS brand heated tobacco products (HTPs) is increasing worldwide; however, little is known about the long-term effects of HTPs aerosol exposure on the lungs. Herein, we exposed C57BL/6 J mice for 24 weeks to clean air, IQOS aerosol, or cigarette smoke, and determined pulmonary function, lung tissue pathology, inflammation, and oxidative stress. Compared with the control group mice, IQOS group mice showed substantially decreased weight and lung function. Levels of IL-6 and TNF-a, as well as oxidative stress markers, were comparable to those found in the cigarette group. In addition, hematoxylin and eosin staining showed that the alveolar space was enlarged and that emphysema had formed in the IQOS group. Masson staining showed that collagen deposition areas were substantially increased in the airway walls in the IQOS group than in the control group. Immunohistochemical staining showed epithelial-mesenchymal transition in the airways of mice in the IQOS group. In conclusion, chronic exposure to IQOS aerosol results in impaired pulmonary function and lung tissue damage; hence, concern should be raised regarding the long-term safety of this product. Highlights: IQOS aerosol exposure results in impaired pulmonary function. IQOS aerosol exposure results in pulmonary emphysema and airway remodeling. IQOS aerosol exposure showed the similar harmful effects compared to traditional cigarette.